Selected Amino Acids Promote Mouse Pre-implantation Embryo Development in a Growth Factor-Like Manner - Morris, Michael B.; Ozsoy, Sukran; Zada, Matthew; Zada, Mark; Zamfirescu, Radu C.; Todorova, Mariana G.; Day, Margot L. (Frontiers in Physiology, 2020)
Groups of amino acids, and some selected amino acids, added to media used for culture of pre-implantation embryos have previously been shown to improve development in various ways including survival to the blastocyst stage, increased blastocyst cell number and improved hatching. In this study, we cultured 1-cell mouse embryos for 5 days to the hatching blastocyst stage in isosmotic medium (270 mOsm/kg) at high density (10 embryos/10 µL), where autocrine support of development occurs, and low density (1 embryo/100 µL), where autocrine support is minimised and development is compromised. When 400 M L-Pro or 1 mM L-Gln was added to embryos at low density, the percentage of embryos reaching the blastocyst stage and the percentage hatching increased compared to low-density culture without these amino acids, and were now similar to those for embryos cultured at high density without amino acids. When L-Pro or L-Gln was added to embryos at high density, the percentage of embryos reaching the blastocyst stage didn’t change but hatching improved. Neither embryo culture density nor the presence of these amino acids had any effect on blastocyst cell number. D-Pro and the osmolytes Gly, and Betaine did not improve embryo development in low- or high-density culture indicating the mechanism was stereospecific and not osmotic, respectively. L-Pro- and L-Gln-mediated improvement in development is observed from the 5-cell stage and persists to the blastocyst stage. Molar excess of Gly, Betaine or L-Leu over L-Pro eliminated improvement in development and hatching consistent with them acting as competitive inhibitors of transporter-mediated uptake across the plasma membrane. The L-Pro effect is dependent on mTORC1 signalling (rapamycin sensitive) while that for L-Gln is not. The addition of L-Pro leads to significant nuclear translocation of p-AktS473 at the 2- and 4-cell stages and of p-ERK1/2T202/Y204 nuclear translocation at the 2-, 4-, and 8-cell stages. L-Pro improvement in embryo development involves mechanisms analogous to those seen with Pro-mediated differentiation of mouse ES cells, which is also stereoselective, dependent on transporter uptake, and activates Akt, ERK, and mTORC1 signalling pathways.